Oral pleasure Kosinski as storyteller - Kosinski, Jerzy N. 1933-1991 (Grove Press, 2012)
A collection of interviews, lectures, and transcriptions of media appearances from the legendary literary figure, offering insight into his work and uncovering his personal history